Volume 1: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-54101
|View full text |Cite
|
Sign up to set email alerts
|

Staged Catalytic Combustion Method for the Advanced Zero Emissions Gas Turbine Power Plant

Abstract: The AZEP (Advanced Zero Emissions Power Plant) project addresses the development of a novel “zero emissions,” gas turbine-based, power generation process to reduce CO2 emissions. Preliminary calculations indicate the attractiveness of this concept in comparison to conventional tail-end CO2 capture. Key to achieving the AZEP project targets is the development of a combustion system to burn natural gas with nearly stoichiometric amounts of oxygen and high levels of exhaust gas dilution. Within the first part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The fuel-rich concept has several advantages compared to the forerunner fuel-lean CST. These include (i) lower catalyst light-off temperatures than that of fuel-lean mixtures [35], which in turn eliminate the preburner of Figure 8.1a, which is a source of NO x emissions; (ii) extended extinction limits [6,20]; (iii) control of catalytic combustion by the oxygen supply, which prevents complete fuel consumption inside the CPO module, even in the event of accidental gas-phase ignition; and (iv) increased stability of the subsequent flame due to the hydrogen content [5]. Similar to CST, the fuel-rich approach provides single-digit NO x emissions and, furthermore, the surface temperature is a moderate function of the fuel-rich stoichiometry [6].…”
Section: Hetero-/homogeneous Combustion In Power Generationmentioning
confidence: 99%
“…The fuel-rich concept has several advantages compared to the forerunner fuel-lean CST. These include (i) lower catalyst light-off temperatures than that of fuel-lean mixtures [35], which in turn eliminate the preburner of Figure 8.1a, which is a source of NO x emissions; (ii) extended extinction limits [6,20]; (iii) control of catalytic combustion by the oxygen supply, which prevents complete fuel consumption inside the CPO module, even in the event of accidental gas-phase ignition; and (iv) increased stability of the subsequent flame due to the hydrogen content [5]. Similar to CST, the fuel-rich approach provides single-digit NO x emissions and, furthermore, the surface temperature is a moderate function of the fuel-rich stoichiometry [6].…”
Section: Hetero-/homogeneous Combustion In Power Generationmentioning
confidence: 99%
“…lower combustion temperatures. Depending on the employed power generation cycle, the fuel can either be syngas with varying H 2 =CO composition, or a mixture of syngas and natural gas diluted with total oxidation products (Griffin et al, 2004;Appel et al, 2005a;Eriksson et al, 2006). Catalytic combustion is an option for all the aforementioned fuels and especially for those cycles involving large EGR due to the resulting low gas-phase reactivity and moderate combustion temperatures of the diluted reaction mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the H 2 O dilution accentuated the homogeneous contribution due to the increased reactivity of the gaseous pathway with increasing water content and the corresponding drop in the catalytic reactivity. The enhancement of the gaseous reactivity can be seen as an advantage for combustion processes that utilize exhaust recycle (Griffin et al, 2004) since the ignition and stabilization of homogeneous combustion is particularly challenging in standard CST of natural gas=air mixtures. The good agreement between measurements and numerical predictions at x ag x x ig (Figure 11(11b, 11c, 12b)) has further suggested that the gas-phase scheme realistically reproduced the pre-ignition gas-phase chemistry.…”
Section: Coupling Of H 2 O and Co 2 With Gaseous Chemistry And Heteromentioning
confidence: 99%
“…In the last years, however, technologies for the efficient combustion of natural-gas and air (or pure oxygen) diluted with large amounts of recycled exhaust gas (H 2 O and CO 2 ) have received increased attention. One such example is the advanced zero emissions power process (Griffin et al, 2004), which aims at mitigating both NO x and CO 2 in power plants. Therein nitrogen is separated from air and natural gas is combusted at moderate temperatures (up to 1500 K) in a stream of oxygen and recycled exhaust gas with the latter comprising up to 90% vol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation